Friction and wear behavior of WS2/Zr self-lubricating soft coatings in dry sliding against 40Cr hardened steel balls - Lian, Yunsong; Deng, Jianxin; Li, Shipeng; Yan, Guangyuan; Lei, Shuting (My University, 2013)
WS[subscript 2] and WS[subscript 2]/Zr self-lubricating soft coatings were produced by medium-frequency magnetron sputtering, multi-arc ion plating and ion beam assisted deposition technique on the cemented carbide YT15 (WC+15%TiC+6%Co) substrates. Microstructural and fundamental properties of these coatings were examined. Sliding wear tests against 40Cr hardened steel using a ball-on-disk tribometer method were carried out with these coated materials. The friction coefficient and wear rates were measured with various applied loads and sliding speeds. The wear surface features of the coatings were examined using SEM. The results showed that the WS-1 specimen (with WS[subscript 2]/Zr composite coating) has higher hardness and coating/substrate critical load compared with that of the WS-2 specimen (only with WS2 coating). The friction coefficient of WS-1 specimen increases with the increase in applied load, and is quite insensitive to the sliding speed. The wear rate of the WS-1 specimen is almost constant under different applied loads and sliding speeds. The WS-1 specimen shows the smallest friction coefficient and wear rate among all the specimens tested under the same conditions. The WS-1 specimen exhibits improved friction behavior to that of the WS-2 specimen, and the antiwear lifetime of the WS2 coatings can be prolonged through adding Zr additives. The self-lubricating and wear mechanism of the WS[subscript 2]/Zr coating was also found from the sliding wear tests.
Keywords: WS2/Zr self-lubricating soft coating; Friction; Wear; Medium-frequency magnetron sputtering; Self-lubricating; Dry sliding